Legal Analysis of the Use of Decentralized Exchange (DEX) in Digital Money Laundering Schemes - Carolina, Lavia Luky; Kholiq, Abdul (Universitas Islam Negeri Alauddin Makassar, 2026)
The use and transaction of crypto assets in Indonesia have grown massively as a form of innovation in digital finance. However, as with any technological advancement, this progress also brings challenges, particularly the risk of crypto assets being misused for money laundering through Decentralized Exchanges (DEX). This study aims to analyze legal certainty and the obstacles to enforcing anti–money laundering (AML) regulations in DEX transactions, which operate outside the supervision of any centralized authority. This research employs a normative juridical method through statutory and conceptual approaches to assess the adequacy of national regulations, particularly the Anti–Money Laundering Law (UU TPPU) and POJK Number 27 of 2024. The findings reveal regulatory gaps, user anonymity, and the cross-jurisdictional nature of DEX transactions, all of which complicate tracing and evidence collection. The study recommends establishing a comprehensive regulatory framework for digital assets, strengthening oversight through legally reachable entities such as centralized exchanges (CEX), wallets, and on–off-ramp services, as well as enhancing the capacity of law enforcement in blockchain forensics to improve the effectiveness of AML enforcement.